HR ANALYTICS MODELLING DALAM RECRUITMENT & CAREER MANAGEMENT PADA INDUSTRI MANUFAKTUR - Alden Nelson; Adeline Oktalia; Emilya; Lia Willyanto; Monica Ella (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Career management is an ongoing series of activities that must be prepared, developed, implemented and monitored by employees or Organizational involvement. The key to creating professional HR lies in recruiting, selecting, training, and developing employees. Therefore, in this study the authors wanted to examine HR analysis related to recruitment and career management. The type of research used by the author is qualitative research, which is carried out based on scientific objects. In this study, the data collected is secondary data. The researcher uses the Observation method, which is the act of analyzing, keeping detailed records of the observable changes that occur in the subjects studied. The author finds that HR Analytics can be used to make a significant difference in business, particularly in the manufacturing sector. These procedures can help businesses grow by reducing the impact of human fatigue on all aspects of business operations and enabling more effective data-driven decision-making.